La adopción de la teoría copernicana por Kepler: un caso de interacción entre ciencia, filosofía y religión - Kozhamthadam, Job (Pontificia Universidad Católica del Perú, 2005)
lt is well known that Johannes Kepler was one of the first reputed and professionally recognized scientists to support the new heliocentric theory of Copemicus. Kepler accepted lt not as a provisional simpler theory, but as the true theory of the universe, and he did so despite the fact that he, more than any one else at that time, was keenly aware of the defects and deficiencies of this new theory. This paper Is an attempt to shed sorne fresh light on this baffling puzzle. After carefully and crltically examining the different views of well-recognized Ke pler scholars, this paper traces the source of this enigma to his special mode of thinking and proceedlng in his sclentlfic inquiry: Kepler allowed a creative and constructlve interaction between scientiflc data, phllosophical principies and certain religious beliefs. lf he had relied on empirícal data alone, he would not have been the most Ioyal Copemican. Philosophical or religious ideas alone also would not have convinced him of the veracity of the heliocenlríc view. Kepler's acceptance of the Copemican system is a paradigm lnstance of the constructive interaction between science, philosophy and religion in the history of science.

Es conocido que Johannes Kepler fue uno de los primeros científicos reputados y profesionalmente reconocidos que apoyaron la nueva teoría heliocéntrica de Copémico. Kepler no la aceptó como una teoría provisional más simple, sino como la verdadera teoría del universo, y lo hizo a pesar del hecho de que él, más que cualquiera de su tiempo, estaba muy consciente de los defectos y deficiencias de esta nueva teoría. Este articulo es un intento de echar una nueva luz sobre este desconcertante rompecabezas. Luego de examinar cuidadosa y críticamente las diferentes perspectivas de académicos kepleríanos bien reconocidos, este articulo halla la fuente de este enigma en su modo especial de pensar y proceder en su investigación clentifica: Kepler permitía una interacción creativa y constructiva entre datos científicos, principios filosóficos y ciertas creencias religiosas. Si hubiese dependido solamente de datos empíricos, él no hubiera sido el copernicano más leal. Las ideas filosóficas o religiosas solas no lo hubiesen convencido de la veracidad del punto de vista heliocéntrico. La aceptación kepleriana del sistema copernicano es una instancia paradigmática de la interacción constructiva entre ciencia, filosofía y religión en la historia de la ciencia.
Kepler's Acceptance of the Copernican Theory: An Interaction of Science. Philosophy, and Religion
Keywords: Kepler; Heliocentrism; Science; Philosophy.; Kepler; Heliocentrismo; Ciencia; Filosofía.; https://purl.org/pe-repo/ocde/ford#6.03.01